Dr. Martin Luther's Deutsche Geistliche Lieder : The Hymns of Martin Luther Set to Their Original Melodies, With an English Version - Luther, Martin, 1483-1546; Allen, Nathan H. (Nathan Hale), 1848-1925; Bacon, Leonard Woolsey, 1830-1907 (Salt Lake City, UT : Project Gutenberg, 1996)
(3z(BDr. Martin Luther's Deutsche Geistliche Lieder(3y (Bby Martin Luther is a collection of hymns set to their original melodies, edited in the context of the Reformation era. The work, likely compiled in the early 16th century, focuses on the importance of congregational singing within the Christian faith, reflecting Luther's broader aims of making religious practices accessible to the common people through the use of vernacular hymns. The opening of this collection includes a mix of hymns and translations, highlighting Luther$1 (Bs conviction that music and song play a vital role in worship and the expression of faith. It presents a variety of hymns, including the well-known (3z(BNun freut euch, lieben Christen g'mein,(3y (Bwhich conveys themes of thanksgiving and salvation through Christ. The introduction emphasizes the transformative power of music, linking it to the Reformation$1 (Bs goal of fostering individual and national identity through worship that resonates with everyday people, further asserting that these hymns are an essential part of spiritual life for Christians. (This is an automatically generated summary.)s
Release date is 1996-02-01
Keywords: Hymns, German; Lutheran Church -- Hymns